"Donating with eyes shut": attitudes regarding DNA donation to a large-scale biobank in Israel. Issue 1 (2nd January 2022) - Raz, Aviad; Hashiloni-Dolev, Yael
Abstract : DNA collection raises ethical, legal, and social issues around privacy, consent, participatory science, benefits and risks, biodata governance, and, ultimately, trust. While there is a consensus that DNA biobanks' success depends on public trust, more evidence is needed regarding the determinants, production, and preservation of such trust. We draw on 14 semi-structured interviews with participants – seven people who donated DNA to an Israeli biobank, and seven who refused to donate; as well as on two focus groups with members of the general public. Our findings call into question the relationship between trust/trustworthiness and donation, suggesting moral strategies termed by respondents as "donating with eyes shut." We conclude by discussing how DNA donation is built on a mixture of attitudes combining criticism, optimism, resistance, and avoiding responsibility as a pragmatic solution to the unresolved conflicts in sharing one's DNA.